The study of maternal and neonatal complications in teenage pregnancy - Suthida Chaithirayanon (2022)
Background: Pregnancy in adolescents is the important health problem around the world, especially for developing countries including Thailand. Objective: To define the prevalence of teenage pregnancy at HRH Princess Maha Chakri Sirindhorn Medical Center as well as its complication in both maternal and neonatal aspects. Materials and Methods: The present study is a prospective cohort study conducted in HRH Princess Maha Chakri Sirindhorn Medical Center, Nakhon Nayok, Thailand. The data was collected between August 2016 and May 2017. Participants were divided into 2 groups consisted of pregnant adolescents (age 10 to 19 years old) and pregnant adults (age 20 to 34 years old). Clinical information of newborns were collected at the age of 3 days. Results: There were 1,258 pregnancies in total including 198 adolescent pregnancies, so the prevalence of adolescent pregnancy in our study was 15.7%. Adolescent pregnancy was associated with lower education level, anemia, and higher rate of vaginal delivery. The neonatal complication of teenage pregnancy found in the present study consisted of anemia (22.7%) and meconium-stained amniotic fluid (9.1%). In contrast, the gestational diabetes (1.5%) and neonatal hypoglycemia (6.6%) were lower in adolescent pregnancy, compared to adult pregnancy. Conclusion: Teenage pregnancy showed the negative impact on both maternal and neonatal health, particularly for anemia in pregnant women and neonates as well as meconium-stained amniotic fluid.